Facilities of radiography, computed tomography and magnetic resonance imaging in diagnostics of tuberculous spondylitis - Sharmazanova, Olena; Deresh, Natalya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
In Ukraine tuberculous spondylitis (TS) occupies a central position within the osteoarticular tuberculosis both by specific weight and severity of the clinical course. Establishing and differential diagnosis of TS remains relevant multimodal problem of beam diagnostics. Objective: to study the possibilities of radiography, computed tomography (CT) and magnetic resonance imaging (MRI ), the advantages of each method for improvement the efficiency of diagnosis of TS. Data of beam diagnostics in dynamics were analyzed in 20 patients examined and treated at the Department of osteoarticular tuberculosis. The indications for using of each method as well as advantages of visualization for improvement of the efficiency in detection and differential diagnosis of spondylitis were defined. Conclusion: only one radiography is not sufficient for diagnostics of TS because negative or questionable data on x-ray films do not exclude disorder in the initial stages. CT and MRI examination have significantly increased the efficiency of diagnostics of TS.